Targeted Inhibition of Pro Inflammatory Slan+ Monocytes Using WGA Functionalized Nanoparticles Encapsulating Itacitinib: A Novel Therapeutic Approach (2024)
Colombia. Ministerio de Ciencia, Tecnología e Innovación - MinCiencias